Becoming a management consultant : key steps to success - Spina, James D. (Emerald points., 2024)
Successful managers lead others to achieve the goals and objectives of the organization where they strive to produce sustainable growth, financial strength, and high job satisfaction. They also simultaneously meet the needs of all stakeholders. Those management consultants who are in high demand are champions for developing the leadership skills needed to make this happen. Each chapter in Becoming a Management Consultant focuses on a different aspect of being a successful management consultant - from effective listening to leadership styles, self-employment, attracting prospective clients, and everything else in between. There are also exercises to be completed to help the reader hone their skills. James D. Spina draws on over forty years first-hand experience as a consultant to equip the reader with this handy guide which appeals to a wide-ranging audience.